Six minor prophets through the centuries. - Coggins, Richard J. 1929-; Han, Jin H. (Malden Wiley-Blackwell, 2011)
"Six Minor Prophets Through the Centuries is the work of highly respected biblical scholars, Jin H. Han and Richard Coggins. The volume explores the rich and complex reception history of the last six Minor Prophets in the exegesis, theology, worship, and arts of Judaism and Christianity, with Han focusing on Nahum, Habakkuk, and Zephaniah, and Coggins on Haggai, Zechariah, and Malachi. This latest title in the outstanding Blackwell Bible Commentary series is the only available text that covers these six prophets within a single volume, providing an essential reference for students, scholars, clergy, and general readers. The Minor Prophets have left a mark disproportionate to their length on the history of biblical reception. Suggestive allusions and references appear throughout ancient, medieval and modern literature, as well as in sculpture and paintings. Each has a special role to play in the Jewish and Christian traditions. Although the six books examined here are known to Christians as Minor Prophets, this epithet refers only to the length of their accounts, and not to their significance to believers, readers, and artists across the centuries"--
Machine generated contents note: Series Editors' Preface.Preface.Table of Contents.Illustrations.Part I. Nahum, Habakkuk, and Zephaniah (Jin H. Han).Introduction.1. Nahum Through the Centuries.Nahum 1.Nahum 2.Nahum 3.2. Habakkuk Through the Centuries.Habakkuk 1.Habakkuk 2.Habakkuk 3.3. Zephaniah Through the Centuries.Zephaniah 1.Zephaniah 2.Zephaniah 3.Part II. Haggai, Zechariah, and Malachi (Richard Coggins).Introduction: Haggai, Zechariah and Malachi within the Hebrew Bible.4. Haggai.5. Zechariah.6. Malachi.Bibliography.Online Sources.Biographies and Glossary.Index of Biblical References.Index of Names and Subjects.
Keywords: Bible. -- Criticism, interpretation, etc; 224.6 -- Kleine profeten--(algemeen)